JINR: the initiator of future discoveries. (8th June 2016) - Matveev, V A
Abstract: On 26 March 2016, the Joint Institute for Nuclear Research (JINR) will mark its 60th anniversary as an internationally known research center that is a unique example of how fundamental theoretical and experimental studies can be integrated with the development and application of cutting-edge technologies and with university education. JINR member states number 18, of which Hungary, Germany, Egypt, Italy, Serbia, and the Republic of South Africa are each under a government-level cooperation agreement with the institute. Three factors combine to form a solid foundation on which JINR bases its work: commitment to traditions of internationally renowned research schools; unique performance hardware capable of solving problems of current interest in various fields of modern physics; and status as a UN intergovernmental body. Ranked high within the world's scientific community, the institute has conducted a wide range of research and trained high quality research personnel for its member states over the 60-years period since its foundation. In accordance with its Charter, JINR is open to participation by all interested states and ensures equal and mutually beneficial cooperation among them.